Improved detection of cortical MS lesions with phase-sensitive inversion recovery MRI. Issue 9 (17th July 2012) - Sethi, Varun; Yousry, Tarek A; Muhlert, Nils; Ron, Maria; Golay, Xavier; Wheeler-Kingshott, Claudia; Miller, David H; Chard, Declan T
Abstract : Objective: Cortical grey matter lesions are common in multiple sclerosis (MS), but usually not seen on MRI. The authors compared the performance of double inversion recovery (DIR, currently considered the best available imaging sequence for detecting cortical lesions) with phase-sensitive inversion recovery (PSIR, a sequence allowing much higher resolution scans to be obtained in a clinically feasible time). Methods: Sixty MS patients and 30 healthy controls underwent MRI scanning on a 3 Tesla scanner. The authors compared intracortical (IC) and leucocortical (LC) lesion counts obtained with a standard DIR sequence (1×1×3 mm resolution, obtained in 4 min) and a PSIR sequence (0.5×0.5×2 mm, 11 min). Lesions were marked separately on DIR and PSIR scans. Results: In the whole MS cohort, more cortical lesions were seen on the higher-resolution PSIR than the DIR scans (IC mean±SD: 18.1±9.8 vs 5.9±4.5, p<0.001; LC mean±SD: 13.4±12.9 vs 7.3±8.0, p<0.001). On PSIR, ≥1 IC lesion was seen in 60/60 MS patients and 1/30 controls, and ≥1 LC lesion in 60/60 patients and 6/30 controls. On DIR, ≥1 IC lesion was seen in 50/60 patients and 0/30 controls, and ≥1 LC lesion(s) in 60/60 patients and 5/30 controls. Conclusions: Compared with DIR, using PSIR the authors are able to detect a significantly greater number of cortical grey matter lesions. The presence of at least one IC lesion in every MS patient, but very few healthy controls, suggests that it may be a useful adjunct to conventional MRI when a diagnosis of MS is suspected but not confirmed.